2007
DOI: 10.1111/j.1551-2916.2006.01314.x
|View full text |Cite
|
Sign up to set email alerts
|

In situ Transmission Electron Microscopy Observation of Multiple Phase Transition in BaGd2Mn2O7

Abstract: In situ transmission electron microscopy observation revealed that BaGd2Mn2O7 undergoes several phase transitions upon heating. The orthorhombic Pnnm phase (I) at room temperature was transformed into a tetragonal P42/mnm (II) at around 420 K via an intermediate phase. On further heating, the other phase (III) nucleated in the phase II matrix at 623 K and grew until covering the whole inspected region by 723 K. Phase III has a 1.5% lattice mismatch along c compared with phase II, and presumably has a monoclini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
4
1
Order By: Relevance
“…12 Recently, however, we have found first-order phase transformations in the BaGd 2 Mn 2 O 7 and BaPr 2 Mn 2 O 7 by using a high-temperature transmission electron microscope (TEM). 13,14 These findings are contradictory to the conventional understanding of the successive phase transformation. We believe that the first-order phase transformation may uniquely occur in layered perovskite with double-block oxygen octahedra.…”
Section: Introductioncontrasting
confidence: 67%
See 1 more Smart Citation
“…12 Recently, however, we have found first-order phase transformations in the BaGd 2 Mn 2 O 7 and BaPr 2 Mn 2 O 7 by using a high-temperature transmission electron microscope (TEM). 13,14 These findings are contradictory to the conventional understanding of the successive phase transformation. We believe that the first-order phase transformation may uniquely occur in layered perovskite with double-block oxygen octahedra.…”
Section: Introductioncontrasting
confidence: 67%
“…Above 277 • C, weak reflections started to appear, as indicated by the arrow in (b), and the intensities grew stronger at 714 • C. The split reflections indicate that the c length of phase III is 1.5% longer than that of the low-temperature phase, as with BaGd 2 Mn 2 O 7 . 13 With increasing temperature, the intensities of the reflections at 11 0 became weaker. Finally, the low-temperature phase disappeared above 750 • C. The repeated in-situ experiments revealed that the transformation speed is temperature-dependent.…”
Section: Resultsmentioning
confidence: 98%
“…With increasing temperature, a new phase III nucleated in the phase II matrix at 623 K. The SAED pattern at 623 K can be interpreted as a mixture of phases II and III, and the coexistence of phases II and III at 623 K was also confirmed by the dark-field images. 43) The coherency between phases II and III was good in the [001] zone. Phase III is sheathshaped with dimensions of several tens of nanometers in width and much longer in length.…”
Section: Jcs-japanmentioning
confidence: 99%
“…Phase III grew until covering the entire inspected region at around 1023 K. The III transition at around 420 K may accompany tilts of the MnO 6 octahedra because the symmetries suggest a change in the octahedral tilt system from (¯00) (0¯0) for P4 2 /mnm to (¯1¯20)(¯2¯10) for Pnnm. 43) On the other hand, the nucleation-growth process observed in the IIIII transition suggests that this is a first-order transition. Actually, the repeated in-situ experiments revealed that the transformation speed is temperature-dependent.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation